PENGEMBANGAN E-LKPD BERBASIS THREE DIMENSIONAL THINKING GRAPH UNTUK MENINGKATKAN LITERASI SAINS - Rahmawati Rahmawati; Ulin Nuha; Zainur Rasyid Ridlo (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Science literacy is an important component in science learning to help students understand science concepts, build science knowledge, and apply it in life. Students' science literacy level is still low and requires further guidance due to learning that does not support students' science literacy skills. The research aims to develop E-LKPD based on Three Dimensional Thinking Graph that is valid, practical, and effective to improve science literacy in junior high school science learning. This research uses development research (Research and Development). The research procedure used is the ADDIE model with the stages of Analyze, Design, Develop, Implement and Evaluate. The product has been applied to students of class VII-C SMP Negeri 6 Jember, with the results that E-LKPD based on Three Dimensional Thinking Graph gets a percentage of 90.5% categorized as very valid, declared very practical getting a percentage of 93.27%, effective to improve science literacy by obtaining an N-gain score of 0.70 which is categorized as high and getting a very good response getting a percentage of 92.52%. This research indicates that E-LKPD based on Three Dimensional Thinking Graph has high validity, is practical in its use, and is effective in supporting junior high school science learning.